2010
DOI: 10.4141/cjss09013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil limestone and foliar manganese and zinc applications on field cauliflower growth and element contents

Abstract: Kowalenko, C. G. and Ihnat, M. 2010. Effects of soil limestone and foliar manganese and zinc applications on field cauliflower growth and element contents. Can. J. Soil Sci. 90: 177Á188. A trial was conducted in a field where a previous study suggested that a deficiency of manganese (Mn) or zinc (Zn) was created by the application of limestone, with the objective to confirm whether lime-induced deficiency is a potential problem in coastal British Columbia acidic soils. The trial involved the application and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 31 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…Foliar applications of Mn and Zn on the cauliflower plants did not affect dry matter yields. Although this would suggest that Mn and Zn did not become deficient with the limestone applications, other work had shown that the type of crop (e.g., cauliflower versus oats) could have influenced the results (Kowalenko 1989), in addition to the possibility that elements other than Mn and Zn became deficient (Kowalenko and Ihnat 2010). Cauliflower tissue analyses showed that limestone increased Ca, decreased Mn, Zn, K, Mg, Na, strontium (Sr) and rubidium (Rb), but did not affect iron (Fe) and copper (Cu) in the plant.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…Foliar applications of Mn and Zn on the cauliflower plants did not affect dry matter yields. Although this would suggest that Mn and Zn did not become deficient with the limestone applications, other work had shown that the type of crop (e.g., cauliflower versus oats) could have influenced the results (Kowalenko 1989), in addition to the possibility that elements other than Mn and Zn became deficient (Kowalenko and Ihnat 2010). Cauliflower tissue analyses showed that limestone increased Ca, decreased Mn, Zn, K, Mg, Na, strontium (Sr) and rubidium (Rb), but did not affect iron (Fe) and copper (Cu) in the plant.…”
mentioning
confidence: 88%
“…The field trial was described in detail by Kowalenko and Ihnat (2010). Briefly, the trial was conducted on an acid soil of silty clay loam texture at Agassiz in the Lower Fraser Valley of coastal British Columbia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations